Barbary Captivity Narratives In Puritan Theology - Mehdi , Rachid (The Journal of Studies in Language, Culture, and Society, 2025)
Barbary captivity narratives have been studied at length by many scholars of early American literature. In an attempt to bring some additional knowledge to this literary genre, instead of dealing with all early Americans’ positions towards the accounts of the captives held in North Africa, we have restricted the field of our study by examining these narratives in relation to a particular Protestant congregation in New England, namely the Puritans, who played a key role in publishing these verbal accounts. The purpose of this article is to show how early American clergymen such as Cotton Mather subjoined these captives’ personal experiences to a Puritan framework of typological hermeneutics for understanding the Bible, not only to fortify their community, but also to build up a cruel picture of North African and Ottoman Muslims as savage and primitive, and legitimize their desire to propagate the Christian faith to those “ignorant” of the “true” knowledge of God.